Working through the fog of a pandemic: Street‐level policy entrepreneurship in times of crises. (6th May 2021) - Gofen, Anat; Lotta, Gabriela; Marchesini da Costa, Marcelo
Abstract: Imposing significant challenges for both street‐level implementation and policy (re)design, crises alter the environment for street‐level policy entrepreneurship (SLPE), wherein street‐level bureaucrats engage in policy formulation processes to secure future policy outcomes. Nevertheless, like street‐level implementation in general, SLPE is studied during ordinary times but rarely during crises. Focusing on community‐health workers in Brazil during the Covid‐19 crisis uncovered a defensive motivation for SLPE, which aimed to legitimize community healthcare as an integral part of pandemic treatment, reforming the government's hitherto neglectful approach to community health services. Moreover, the continuing crisis created an unusually prolonged window of opportunity for securing community healthcare provision. By utilizing collective efforts and drawing on powerful politicians' mobilization, SLPE during crisis shares similarities with, yet differs from, SLPE during ordinary times, while further closing the interstices between local, professional, and political perspectives in the formulation of policy decisions.